Operadores lineares Cohen fortemente somantes - Leite, Fábio da Silva de Siqueira (2017)
The goal of our work is to study the class of the Cohen strongly summing operators. Initially, we present basic results from Functional Analysis that are necessary for the development of the text and then we deal with sequence spaces which will be used to de ne and study the classes of operators involved in this work, as necessarily the class of the absolutely summing operators. We also study the sequence space of the Cohen- Khalil strongly (q; p)-summable sequences and the sequence space of the Cohen strongly p-summable sequences, as a particular instance of the former. From this, we de ne the class of the Cohen strongly p-summing operators and the class of the Cohen-Khalil strongly (s; r; p)-summing operators which, under certain conditions, are equivalent. We conclude with a study, from the viewpoint of the operator ideal theory, using the abstract environment created by G. Botelho and J. R. Campos, in order to show that p and Dp are Banach ideals and the relations dual p = Dp and Ddual p = p are valid, where p and p are conjugate indexes.